2017
DOI: 10.34068/jscwr.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modeling Flow Rates in Tidal Creeks: A Case Study from the Central Coast of South Carolina

Abstract: The purpose of this study was to collect site- and condition-specific hydrology data to better understand the water flow dynamics of tidal creeks and terrestrial runoff from surrounding watersheds. In this paper, we developed mathematical models of tidal creek flow (discharge) in relation to time during a tidal cycle and also estimated terrestrial runoff volume from design storms to compare to tidal creek volumes. Currently, limited data are available about how discharge in tidal creeks behaves as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, maintaining appropriate water flows may limit the growth or transport of Salmonella . Such an assessment could be accomplished by stormwater runoff models (Blair et al., 2012; Ellis et al., 2017). Salmonella spread through the feces of infected humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, maintaining appropriate water flows may limit the growth or transport of Salmonella . Such an assessment could be accomplished by stormwater runoff models (Blair et al., 2012; Ellis et al., 2017). Salmonella spread through the feces of infected humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…). Detailed geographic information system land cover assessments, and therefore degree of development for each watershed surrounding study sites, are provided as separate contributions (Ellis ; Ellis et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Both of these conditions can significantly affect residence times, and it is interesting to note that hydrologic alteration is now being considered as a source of pollution within the USEPA Clean Water Act (Novak et al 2016). Ellis et al (2017) suggested that creeks with relatively large discharge volumes could more efficiently dilute contaminant concentrations from terrestrial runoff compared to smaller, more urbanized creeks, suggesting the latter are more vulnerable to increased runoff from developed landscapes. Very few creeks in our study had both gaged flows and bathymetric data to estimate residence times, which is a current data gap critical to better understanding the role of freshwater discharge as a physical driver of water quality dynamics.…”
Section: Discussionmentioning
confidence: 99%